Impacts of Microplastic Pollution in Freshwater System in Kampung Jambu Lapan, Negeri Sembilan - NUR FAQIHAH IZZATI RAMLI; MOHD ARIF ROSLI (Progress in Engineering Application and Technology, 2026)
The problem of microplastic contamination in freshwater systems is now one of the main environmental challenges, as it is irreversible and may have ecological and human health effects. This paper examines the occurrence, characteristics, and polymer composition of microplastics within a freshwater habitat at the confluence of the Muar and Jempol Rivers, Kampung Jambu Lapan, Negeri Sembilan, Malaysia. Surface water sampling was conducted in both dry and rainy weather to determine seasonal variability. Laboratory analysis included filtration, separation using saturated sodium chloride solution, chemical digestion, stereo microscope observation, and Fourier Transform Infrared (FTIR) analysis of polymers. The findings showed that microplastics were present in all samples and were abundant during rainy weather, supporting the hypothesis that surface runoff plays a role in the transport of microplastics. The most prevalent morphology was fibres, followed by fragments, with the majority of particles measuring less than 1mm in length. FTIR identified polydimethylysiloxane (PDMS) as the common polymer, indicating domestic and urban-related sources. This study highlights the importance of hydrologic conditions in influencing the distribution of microplastics and emphasizes the need to monitor and implement source-control measures to reduce freshwater contamination.